Reconstitution of the human U snRNP assembly machinery reveals stepwise Sm protein organization - Neuenkirchen, Nils; Englbrecht, Clemens; Ohmer, Jürgen; Ziegenhals, Thomas; Chari, Ashwin; Fischer, Utz (The EMBO journal, 2015)
The assembly of spliceosomal U snRNPs depends on the coordinated action of PRMT5 and SMN complexes in vivo . These trans ‐acting factors enable the faithful delivery of seven Sm proteins onto snRNA and the formation of the common core of snRNPs. To gain mechanistic insight into their mode of action, we reconstituted the assembly machinery from recombinant sources. We uncover a stepwise and ordered formation of distinct Sm protein complexes on the PRMT5 complex, which is facilitated by the assembly chaperone pICln. Upon completion, the formed pICln‐Sm units are displaced by new pICln‐Sm protein substrates and transferred onto the SMN complex. The latter acts as a Brownian machine that couples spontaneous conformational changes driven by thermal energy to prevent mis‐assembly and to ensure the transfer of Sm proteins to cognate RNA. Investigation of mutant SMN complexes provided insight into the contribution of individual proteins to these activities. The biochemical reconstitution presented here provides a basis for a detailed molecular dissection of the U snRNP assembly reaction. Synopsis By reconstituting the assembly of human U snRNPs in vitro , this study establishes the sequential action of distinct Sm protein complexes and provides a basis for understanding defects in Spinal Muscular Atrophy. Reconstitution of the human snRNP assembly machinery from recombinant proteins. The PRMT5 complex acts as a scaffold for the stepwise organization of Sm proteins by the assembly chaperone pICln. Release of pICln‐Sm protein intermediates from the PRMT5 complex scaffold is feed‐forward‐driven by new pICln‐Sm protein precursors. The SMN complex acts as a Brownian machine, which enables Sm proteins to proofread cognate snRNAs and catalyzes faithful snRNP assembly. Spinal muscular atrophy‐causing mutations differentially affect snRNP assembly. Graphical Abstract By reconstituting the assembly of human U snRNPs in vitro , this study establishes the sequential action of distinct Sm protein complexes and provides a basis for understanding the defects in spinal muscular atrophy.